PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADTOGETHER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 106820 PANCUR BATU - Romian H.J Simamora; Patri Janson Silaban; Antonius Remigius Abi; Darinda Sofia Tanjung; Anton Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the influence of the Numbered Head Together type cooperative learning model. The research results show that the average mathematics learning result for class IV is 81.2 in the good category. Of the 25 students studied, 19 students (76%) met the Minimum Completion Criteria (KKTP), while 6 students (24%) did not meet the KKTP. This research is a type of quantitative research which aims to determine the effect of the Numbered Head Together type cooperative learning model on the mathematics learning outcomes of class IV students at SDN 106820 Pancur Batu. The population is all class IV students, totaling 25 students. Samples were taken based on a saturated sampling technique, namely 25 students. Student learning results show that the average score for class IV pre-test students is 66.88 while the post-test score is 81.2. The results of this research show that students' mathematics learning outcomes using the Numbered Head Together cooperative learning model are included in the strong category with a correlation coefficient of 0.974, which means rcount (0.974) ≥ rtable (0.396), so Ha is accepted. Next, testing the hypothesis shows that tcount is 20.435, while ttable is 2.060, so it is proven that the hypothesis is greater than ttable, so Ho is rejected and Ha is accepted. So it can be concluded that the Numbered Head Together (X) type cooperative model has a positive and significant influence on learning outcomes (Y). This shows that there is an influence of the Numbered Head Together type cooperative learning model on students' mathematics learning outcomes. Thus, all questionnaire instruments in this study were declared reliable and trustworthy, because they met the minimum requirements that had been determined.